2002
DOI: 10.1093/chemse/27.8.747
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Wine Expertise: Olfactory Threshold, Perceptual Skill and Semantic Memory in Expert and Novice Wine Judges

Abstract: We investigated recognition and identification of wine-relevant odours as a function of domain-specific expertise. Eleven wine experts and 11 wine novices participated in tasks measuring olfactory threshold, odour recognition, odour identification, and consistency of odour naming. Twenty-four wine-relevant odorants were sampled orthonasally by each participant in the semantic (identification; consistency of naming) and episodic (recognition) memory tasks. Results showed superior olfactory recognition by expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
179
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(194 citation statements)
references
References 27 publications
13
179
1
1
Order By: Relevance
“…Experts were defined in accordance with previous studies (Melcher and Schoeler, 1996;Bende and Nordin, 1997), using criteria outlined in Parr et al (2002). A person was defined as an expert if they fitted at least one of the following categories:…”
Section: Participantsmentioning
confidence: 99%
“…Experts were defined in accordance with previous studies (Melcher and Schoeler, 1996;Bende and Nordin, 1997), using criteria outlined in Parr et al (2002). A person was defined as an expert if they fitted at least one of the following categories:…”
Section: Participantsmentioning
confidence: 99%
“…Instead the professional wine experts were asked to fill individually the questionnaires according to their prototypical long-term memory of each PGI red wine sensory profile, this method to be considered feasible and challenging to characterize macro-zoning or nationwide spaces. A restrictive approach to Parr (Parr et al, 2002) has been made to select expert respondents. The questionnaire was designed according to the classical three-tier sensory method of assessment: visual, aromatic and gustatory/tactile attributes (Noble et al, 1987;Fischer et al, 1999;Gawel et al, 2000;Gawel et al, 2001;Hernández et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies (Solomon 1990(Solomon , 1997 have shown that sommeliers surpass by far novices when it comes to associate and identify wines. Others (Bende and Nordin 1997;Parr et al 2002) have found no meaningful difference between the discriminatory performances of the expert and the novice. Though results rarely concur, most researchers readily admit that sommeliers are experts of sorts endowed with a remarkably dense lexical system.…”
Section: Testing Taste: Experimental Studiesmentioning
confidence: 96%